A Second-Order Method for the Numerical Integration of a Size-Structured Cell Population Model - O. Angulo; J. C. López-Marcos; M. A. López-Marcos (Abstract and Applied Analysis)
We consider the numerical integration of a size-structured cell population model. We propose a new second-order numerical method to attain its solution. The scheme is analyzed and the optimal rate of convergence is derived. We show experimentally the predicted accuracy of the scheme.